Enhancing undergraduate physiotherapy experience: assessing learning satisfaction, interpersonal skill development, and character growth through early fieldwork - Hafifi Hisham; Mohd Azzuan Ahmad; Nor Azura Azmi; Nor Azlin Nordin (Penerbit Universiti Kebangsaan Malaysia, 2023)
Field research entails collecting data and conducting studies in real-world settings to gain beneficial knowledge. However, fieldwork presents its difficulties, such as logistical constraints, unknown variables, and the need for adaptability to acquire accurate and reliable data. The objective of this research is to analyze the experience among undergraduate physiotherapy students when exposed to early fieldwork by assessing the level of learning satisfaction, and interpersonal and character growth outcomes. This study utilized a cross-sectional study design with a single group assessment taken in July 2023. Surveys were conducted by utilizing the Field Study Learning Satisfaction Survey Questionnaire among 1st and 2nd year physiotherapy students (n=26) at Universiti Kebangsaan Malaysia (UKM). The findings demonstrate an increase in the satisfaction level, interpersonal and character growth after participating in the fieldwork program. In conclusion, this study highlights the positive impact of early fieldwork on the undergraduate physiotherapy experience, specifically in terms of learning satisfaction, interpersonal skill development, and character growth.